2013
DOI: 10.1186/1478-7547-11-13
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionate utilization of healthcare resources among veterans with COPD: a retrospective analysis of factors associated with COPD healthcare cost

Abstract: BackgroundCOPD is a significant cause of morbidity and mortality in the Veterans Health Administration (VHA). To determine the clinical factors associated with the cost of COPD management, we analyzed the relationship between clinical characteristics and COPD healthcare costs at the Cincinnati VAMC.MethodsWe queried the VHA Decision Support System for patients diagnosed with COPD at the Cincinnati VAMC and calculated their VHA COPD-related encounters and costs in FY2008. Patients were ranked by COPD-related co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…HCC categories were grouped into 5 major chronic disease groups for risk adjustment: Cerebral (HCC 097–099), Heart (HCC 083–084), Vascular (HCC 104–105), Cancer (HCC 007–010), Diabetes (HCC 015–020) and Arrhythmias (HCC 092–093). These conditions are common among veterans and are associated with higher costs of care [1821]. A patient might be found in multiple conditions, if more than one was documented.…”
Section: Methodsmentioning
confidence: 99%
“…HCC categories were grouped into 5 major chronic disease groups for risk adjustment: Cerebral (HCC 097–099), Heart (HCC 083–084), Vascular (HCC 104–105), Cancer (HCC 007–010), Diabetes (HCC 015–020) and Arrhythmias (HCC 092–093). These conditions are common among veterans and are associated with higher costs of care [1821]. A patient might be found in multiple conditions, if more than one was documented.…”
Section: Methodsmentioning
confidence: 99%
“…Three models specified COPD-related costs by age. Several studies investigated the association between age and COPD-related costs and found no significant impact of age on costs [43][44][45][46]. This may be because age and FEV1% predicted are correlated and in three of these studies FEV1% was also included in the multivariate model and found to be a significant predictor.…”
Section: Discussionmentioning
confidence: 99%
“…These Veterans have worse lung function but similar frequencies of co-morbidities. 4 This group of Veterans practices greater self-management and is more likely to treat episodes of breathlessness by increased utilization of inhalers, nebulizers, steroids/antibiotics, and more frequent visits to the urgent care clinic or the ED.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that the stratification of these patients by healthcare costs correlates with the severity of disease measured by spirometry and comorbidities. 4 This research protocol was approved by the Cincinnati VAMC Research and Development Committee and the University of Cincinnati Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation